2009
DOI: 10.1073/pnas.0902191106
|View full text |Cite
|
Sign up to set email alerts
|

An age-related homeostasis mechanism is essential for spontaneous amelioration of hemophilia B Leyden

Abstract: Regulation of age-related changes in gene expression underlies many diseases. We previously discovered the first puberty-onset gene switch, the age-related stability element (ASE)/age-related increase element (AIE)-mediated genetic mechanism for agerelated gene regulation. Here, we report that this mechanism underlies the mysterious puberty-onset amelioration of abnormal bleeding seen in hemophilia B Leyden. Transgenic mice robustly mimicking the Leyden phenotype were constructed. Analysis of these animals ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…Interestingly, DFCR-RE2 contains two sequences similar to this ASE, namely GAGGCAG, in its middle region. Mutational studies demonstrated that this sequence (GAGGCAG) does not bind to any proteins present in nuclear extracts, including Ets1 [25]. Further studies are needed to determine whether there is a functional relationship between the ASE and DFCR-RE2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, DFCR-RE2 contains two sequences similar to this ASE, namely GAGGCAG, in its middle region. Mutational studies demonstrated that this sequence (GAGGCAG) does not bind to any proteins present in nuclear extracts, including Ets1 [25]. Further studies are needed to determine whether there is a functional relationship between the ASE and DFCR-RE2.…”
Section: Resultsmentioning
confidence: 99%
“…Kurachi et al [24,25] identified an age-related stability element (ASE) that regulates age-related gene expression. They found an ASE, (C/G)AGGAAG, containing an Ets transcription factor consensus motif (GGAA), that was bound specifically by Ets1.…”
Section: Resultsmentioning
confidence: 99%
“…8A, Con Ppp2ca, lane 7). This type of result, where the addition of antibody does not result in a supershift, still indicates specific binding and has been previously observed (36,37). Binding was specific because no binding was observed to a mutated SRE in the presence of antibody (Fig.…”
Section: Pp2a Is Required For Srebp-2 Dna Binding To a Ldlr Sre In Rementioning
confidence: 62%
“…In this talk we will review some of our recent results in this area [4]- [14] obtained in collaboration with T. Appelquist, M. Piai, N. Christensen, and M. Kurachi. (The work with Kurachi is also discussed in his talk [15]. )…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Refs. [28] and [13] have used solutions of Schwinger-Dyson and Bethe-Salpeter equations to evaluate S [15].…”
Section: Precision Electroweak Constraintsmentioning
confidence: 99%